Poster Presentations 2020
DOI: 10.1136/jech-2020-ssmabstracts.166
|View full text |Cite
|
Sign up to set email alerts
|

P74 Barriers and facilitators for preconception planning among women in the United Kingdom: a rapid review

Abstract: Background Preconception planning enables women to optimize preconception health thereby reducing the risk of poor maternal and neonatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…National Institute for Health and Care Excellence (NICE) guidelines recommend that all pregnant women are seen for their first antenatal appointment within the first ten weeks of pregnancy 14 . A UK rapid review of barriers and facilitators to preconception care identified limited evidence among migrant women, with almost all studies undertaken in non-migrant populations 15 . Despite the potential for higher preconception risks among migrant women, and known links between preconception risks and pregnancy outcomes, no previous studies have compared migrant and non-migrant women's preconception health in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…National Institute for Health and Care Excellence (NICE) guidelines recommend that all pregnant women are seen for their first antenatal appointment within the first ten weeks of pregnancy 14 . A UK rapid review of barriers and facilitators to preconception care identified limited evidence among migrant women, with almost all studies undertaken in non-migrant populations 15 . Despite the potential for higher preconception risks among migrant women, and known links between preconception risks and pregnancy outcomes, no previous studies have compared migrant and non-migrant women's preconception health in the UK.…”
Section: Introductionmentioning
confidence: 99%